Large myofascial fibromatosis involving the shoulder girdle. - Bhaskar A (Journal of Postgraduate Medicine, 1994)
An 11 year old girl presented with gradually increasing swelling over left scapular region and limitation of movements. On examination, a mass with firm to hard consistency was found fixed to the scapula. Clinical diagnosis of fibromatosis was confirmed by needle biopsy. Radical excision of the tumor was carried out and the resultant large exposed area was covered by transpositional rotation of trapezius myocutaneous flap. Microscopic examination of excised tumor revealed spindle shaped elongated cells in the form of whorls and trabeculae. The post operative course of the patient was uneventful with no evidence of recurrence at the end of 22 months.